Performance evaluation criteria"Applied Study in the General Company for the manufacture of glass and ceramics" - نعمان, لبنى هاشم (Journal of Economics and Administrative Sciences, 2011)
Contemporary management is interested in the process of performance assessment  because of its significance in the field of planning and controlling the multiactiveties to attain its goals and uncovering digression of virtual performance after comparing it with the plan or equitable performance.Digression is analyzed to enable management control centers of authority.Assessment process significance is closely related by setting definite categories to evaluate the economic activity to know the ability to achieves aims.This study concentrated on the most important categories that used to evaluate  company understudy with ather categories suggested to complete assessment process.This study is in three chapters , the first explains assessment performance, its concept, aims, basis and considerations in setting categories.Chapter two deals with use of categories in auditing and performance efficiency .Chapter three includes a historical briefing about the firm, data system available, its performance efficiency, conclusions and recommendations